Диджиталізація бізнесу як дієвий інструмент комунікативної політики підприємства - Іпполітова, Інна Ярославівна; Момотков, Ігор Сергійович; Прокопович, Світлана Валеріївна (Міжнародний університет фінансів, 2024)
У статті досліджено сутність поняття «диджиталізація» та який зміст вкладають науковці у цю дефініцію. Проведено аналіз використання інформаційно-комунікаційних технологій та запровадження електронної торгівлі підприємствами за видами економічної діяльності й розподілом за кількістю зайнятих працівників. Зазначено, що окремою складовою диджиталізації доцільно виділити маркетинг, а саме комунікативну політику підприємства. Перераховано додаткові можливості, які надає диджиталізація бізнесу для здійснення ефективної комунікації з усіма стейкхолдерами, забезпечуючи більш швидку, точну та персоналізовану взаємодію з клієнтами. Визначено основні причини появи опору заходам з диджиталізації та основні способи їх подолання. Наведено переваги та можливості, які буде мати бізнес після подолання опору працівників до заходів щодо диджиталізації бізнесу у вигляді значного позитивного впливу на розвиток підприємства.

The article is devoted to the study of the use of digitalization in the process of implementing the communication policy of an enterprise. Thanks to the use of digital marketing tools, a competitive advantage is created that is difficult to replicate, thereby attracting more customers and partners. During the research process, the following general scientific research methods were used: theoretical generalization, analysis, synthesis, and induction. The essence of the concept of “digitalization” and the various meanings that scientists attribute to this definition are analyzed. An analysis was conducted on the use of information and communication technologies and the adoption of e-commerce by enterprises across different types of economic activities and distributions based on the number of employed workers. It is noted that marketing should be highlighted as a separate component of digitalization, specifically the communication policy of the enterprise. This study details which digital tools should be used to implement effective communication policies. The additional opportunities that business digitalization provides for effective communication with all stakeholders are listed, ensuring faster, more accurate, and personalized interaction with customers. By introducing digital technologies and automating routine tasks, it was noted that an enterprise can significantly speed up its business processes, reducing task completion time and increasing work efficiency. Staff will be able to focus on more meaningful, creative, and unique tasks, increasing productivity and the quality of work done. Digitalization aims to expand markets and customer bases by increasing customer engagement through online platforms and digital channels. The main reasons for resistance to digitalization measures and the primary ways to overcome them are identified. The advantages and opportunities that a business will have after overcoming employee resistance to digitalization measures are presented, highlighting the positive impact on enterprise development. The practical significance of the article lies in the potential for implementing the recommended digital tools into the practical activities of an enterprise.
Digitalization of business as an effective tool for enterprise communication policy
Keywords: диджиталізація; інформаційно-комунікаційні технології; електронна торгівля; комунікативна політика; опір працівників до заходів щодо диджиталізації бізнесу; digitalization; information and communication technologies; e-commerce; communication policy; employee resistance to business digitalization measures